Which equation written in two variables is equivalent to this function? f(x) = -2(x – 4) y = -2(f(x) – 4) y =

Question

Which equation written in two variables is equivalent to this function?

f(x) = -2(x – 4)

y = -2(f(x) – 4)
y = -2x + 4
y = -2(f(x) + 4)
y = -2(x – 4)

in progress 0
Natalia 2 hours 2021-09-13T06:19:38+00:00 2 Answers 0

Answers ( )

    0
    2021-09-13T06:21:09+00:00

    I think that the correct answer would be the second option :y=-2x+4

    0
    2021-09-13T06:21:32+00:00

    Ploto User

    Answer:

    Select the correct answer.

    Which equation written in two variables is equivalent to this function?

    y = -2(x – 4)

    Step-by-step explanation:

    Explanation:

    In a function with x as the independent variable and y as the dependent variable, the f(x) notation replaces y in the equation.

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )